162k views
4 votes
I am trying to remember how to do Write a two-column proof,

Given: a = 2b + 6

a = 9b - 8


Prove: b = 2

1 Answer

5 votes

9514 1404 393

Step-by-step explanation:

Make use of the properties of equality.

a = 2b +6 . . . . . given

a = 9b -8 . . . . . given

2b +6 = 9b -8 . . . . . . . substitution property of equality

6 = 7b -8 . . . . . . . . . . . subtraction property of equality

14 = 7b . . . . . . . . . . . . . addition property of equality

2 = b . . . . . . . . . . . . . . . division property of equality

b = 2 . . . . . . . . . . . . . . symmetric property of equality

User Marktani
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.